Degradation of diesel fuel by Pseudomonas aeruginosa B031 with expression of the alkB gene in a column bioreactor - Daris, Pieter Jhon Joshua; Wilopo, Wahyu; Warmada, Wayan; Retnaningrum, Endah (Journal of Degraded and Mining Lands Management, 2024)
Diesel fuel pollutants contain toxic hydrocarbons dominated by aliphatic and aromatic hydrocarbons. Hydrocarbon pollutants can be degraded in an environmentally friendly manner through bioremediation using hydrocarbonoclastic bacteria, i.e., Pseudomonas aeruginosa B031, which harbors the alkB gene that encodes an alkane hydroxylase that degrades alkane chains in hydrocarbons. This study compared the ability and efficiency of P. aeruginosa B031 to degrade diesel pollutants in a batch system and a continuous system using a column bioreactor, as well as the expression of alkB. P. aeruginosa B031 could more efficiently degrade diesel fuel in a continuous system in a column bioreactor than in the batch system. The concentrations of phenol, total organic carbon, chemical oxygen demand, and biological oxygen demand in the column bioreactor underwent a greater decrease than those in the batch system, namely 1.5-fold, 1.7-fold, 1.4-fold, and 1.3-fold, respectively. The decrease in these concentrations was followed by changes in functional groups, as shown via Fourier transform infrared spectroscopy. The number of bacteria and the concentration of exopolysaccharide increased in the column bioreactor by 4-fold and 2.3-fold more than the increase in the batch system. The ability of P. aeruginosa B031 to degrade diesel fuel in the column bioreactor was also demonstrated by the higher expression of alkB than that in the control.